Petinštirideset let nevroleptikov - Šteblaj, Anton (Medicinski razgledi, 1996)
Neuroleptics were discovered by chance in 1950. Since then, a substantial bodyof clinical experiences has been collected. The understanding of mechanisms of their action stimulated the development of new theories about the causes of mental disorders. Neuroleptics are symptomatic drugs, because they do not affect the principal causes of mental disorders. The authors give a brief historical review of the development of neuroleptics, and discuss in detail their pharmacokinetics, mechanisms of action and side effects. Clinicalefficacy of neuroleptics is illustrated by a number of examples, and some guidelines for a rational use of these drugs are given. Polypharmacy should be avoided and the dosage individualised. The patient's response to treatment should be evaluated no sooner than four to six weeks after the initiation of therapy. The authors review the latest achievements in the search for new neuroleptics, which are excepted to treat more effectively negative manifestations of schizophrenia and to cause fewer side effects.
Keywords: psihoze; duševni bolniki; therapy; zdravljenje; zdravila; drug